Embryonic and Larval Development Stages of the African Catfish Clarias gariepinus (Burchell, 1822) (Teleostei, Clariidae) in The Ouargla, Algeria - Ibrahim elkhalil BEHMENE; Benabdallah Bachir Bouiadjra; Miloud Attou; Abdelkader Homrani (Journal of Aquaculture and Fish Health, 2022)
This study was designed to investigate for the first time in the region of Ouargla, Algeria, the events and timing of the embryonic development of African catfish, C. gariepinus  (Burchell, 1822). The embryonic development was carefully monitored using a binocular magnifier 10 and 20 lenses that reveal details on live specimens from fertilization to the first take of food. The offensive and foul odor continues to be the characteristic smell of the hatching stage. Pigmentation and continuous spread of cephalo-caudal melanophore in fry hatched on the first day. The barely hatched larvae are photo-phobic. The yellow reserve is reduced and leads to the ability to swim easily, and the majority starts feeding on the fourth day. The vitellin reserve is significantly reduced, allowing the larvae to feed exogenously. The events observed in our opinion demonstrate the presence of two exceptionally critical parameters: the use of a high-quality diet and the guarantee of a clean and quality source of water, meeting the standards of aquaculture farming.